Gleason drift in the NIHR ProtecT study. Issue 3 (7th January 2015) - Oxley, Jon; Simpkin, Andrew; Goepel, John; Varma, Murali; Griffiths, David; Grigor, Ken; Mayer, Nick; Warren, Anne; Deshmukh, Nayneeta; Bhattarai, Selina; Dormer, John; Hounsome, Luke; et al.
<x xml:space="preserve">Abstract</x> Aims There is increasing evidence of Gleason score (GS) drift in prostatic core biopsies during the last two decades. The ProtecT study is a randomized controlled study and provides an excellent cohort to study the effect of time, prostate‐specific antigen (PSA) level, perineural invasion, tumour length and age on GS. Methods and results The ProtecT study recruited men in the United Kingdom between 1999 and 2010. The Gleason scores were grouped into four categories ≤3 + 3, 3 + 4, 4 + 3 and ≥4 + 4 for analysis. Data from England between 2000 and 2012 were also available. A total of 3282 biopsies containing cancer were analysed. For each year of the ProtecT study, the odds of being diagnosed with a higher GS category increased by 4.9%. Higher GS was also associated with perineural invasion, increasing tumour length, age and PSA level. While biopsy GS from England was incomplete, it also showed a marked decrease in GS five and six tumours during the same period. Conclusion There was GS drift from 3 + 3 to 3 + 4 with time in the ProtecT study, but there appeared to be no significant change in percentage of GS 4 + 3 or higher. This drift was less dramatic when compared to GS in the rest of England.